Clinical Initial Response of Neoadjuvant Chemotheraphy in Triple Negative, HER-2, and Luminal Types of Breast Cancer in Denpasar (A Preliminary Study) - Yarso, K. Y.; Sudarsa, I W; Wibawa-Manuaba, I B. T (BALI MEDICAL JOURNAL, 2012)
Objectives: Triple Negative, Luminal, HER-2 subtypes of breast cancer are markers to predict behavior, aggressiveness, and response to chemotherapy. The aim of this study is to understand character and response to standard neoadjuvant chemotherapy in different subtypes of breast cancer. Method: This is a descriptive study of breast cancer subtypes. From 687 patients (2003-2010) 351 patients have IHC data which divided into 3 groups, Triple negative, Luminal, and HER-2. We used 10% as a cut off point for ER, PR, while 30% & positive 3 for HER-2. We determined initial clinical response after 3 cycles of neoadjuvant chemotherapy although only 77 got standard neoadjuvant chemotherapy and had clinical response data. We used 50% diameters depreciation & no metastasis as cut off point for respond group. Results: There were 116 (33%) Triple Negative, 60 (17%) HER-2, and 175 (50%) Luminal Subtypes. The mean of age for 351 patients are 48.32 (23-82) years. In this study, it was obtained that no significant difference of means of age (p=0.24) in these 3 groups. Triple negative group significantly more advance in grade if compared with the other two groups (p=0.02). HER-2 group had highest response with standard neoadjuvant chemotherapy (50%), Luminal group had (49%), and Triple negative group had only (15%) response. One pCR in HER-2 group. There were no difference ages in subtypes.  Triple negative has more advances in grade. HER-2 group has highest response to standard neoadjuvant chemotherapy and Triple negative has lowest response to standard neoadjuvant chemotherapy.